2015
DOI: 10.1016/j.renene.2015.04.059
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of biomass plants – Results of a longitudinal study in the bioenergy-region Altmark

Abstract: a b s t r a c tThe present contribution addresses the results of a longitudinal study in a 'bioenergy-region' concerning the public acceptance of biomass plants and the corresponding influencing factors. Using a standardized questionnaire, 423 persons were polled between 2009 and 2011 on three points of measurement in four places in the bioenergy-region Altmark. One main result of the study is that the reported public acceptance remains constantly high over time; nevertheless it became evident that the respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 24 publications
(34 reference statements)
1
28
1
3
Order By: Relevance
“…Contrary to other studies on the acceptance of biogas plants (Kortsch et al, 2015;Schumacher and Schultmann, 2017;Soland et al, 2013), we heard very little mention of smell. This may be explained both by the evolution of the technology, and by the use, in the four studied farms, of a mix of cow manure and agro-industrial or agricultural wastes.…”
Section: The Location and Social Acceptance Issuescontrasting
confidence: 95%
See 1 more Smart Citation
“…Contrary to other studies on the acceptance of biogas plants (Kortsch et al, 2015;Schumacher and Schultmann, 2017;Soland et al, 2013), we heard very little mention of smell. This may be explained both by the evolution of the technology, and by the use, in the four studied farms, of a mix of cow manure and agro-industrial or agricultural wastes.…”
Section: The Location and Social Acceptance Issuescontrasting
confidence: 95%
“…Policies for biofuel development (Borras et al, 2011;Hultman et al, 2012) in rural areas are analysed to verify opportunities, through the development of biomass, to diversify economies and increase farmers' incomes (Mwakaje, 2012;Zolin, 2011). On the other hand, some recent studies question the scale of production (Carrosio, 2013;Cotula, 2012;Monteleone et al, 2009) and pay more attention to the local acceptance of biogas plants (Kortsch et al, 2015;Schumacher and Schultmann, 2017;Soland et al, 2013). Local systems based on ecological principles have been analysed (Altieri, 1999;Huttunen, 2011), as have the driving forces of and attitudes towards biofuel diversification (Frantal and Prousek, 2016).…”
Section: The Territorial Dimension and The Spatial Scalementioning
confidence: 99%
“…It depends on personal experience and emotions (Kortsch et al 2015). Quantification of these values should therefore take into account the entire life cycle of a forest or comparison among forests of different ages.…”
Section: Model Approach and Data Inputmentioning
confidence: 99%
“…Biomass is proven as a labor intensive technology and it has huge potential to create employment [11]. Therefore, the regional unemployment rate also amplifies the impact of developing biomass technology on the economy [19].…”
Section: Effect On Employmentmentioning
confidence: 99%
“…Svanberg et al [3] directly pointed out that the cooperation between stable owner and energy company is needed to support the commercialization of conversion technology. What is more, the lack of public participation always results in the social amplification of the negative image of biomass technology, which is the main reason why the local residents feel anxious about the new biomass project and thus leads to failure [19,20]. Gasparatos et al [21] demonstrated that the impact of incomplete understanding of biomass fuel is one of the most critical barriers in the development of biomass investments through a case study in the continent.…”
Section: Introductionmentioning
confidence: 99%